A STUDY ON IMPACTS AND MANAGEMENT OF INDUSTRIAL WASTE - Yadav, Kavita; Sharma, Shalini; Pathak, Vishal (Universal Research Reports, 2018)
Strong economic growth, urbanisation, and growing populations have led to an increase in (materially intensive) resource utilization, as well as the discharge of vast volumes of trash into the environment. Globally, present waste and resource management lacks a comprehensive approach that encompasses the entire product design, raw material harvest, manufacture, usage, recycle, & waste management cycle. Advances and various sustainability problems facing the worldwide waste management system are described and explored in this article. Waste management in the future will demand a more systems-oriented framework that includes the fundamental causes of problems in order to manage resources & wastes responsibly. The production of improved feedback information (statistics) on how trash generation is connected to consumption is a specific challenge to address.